Approved checkpoint inhibitors in bladder cancer: which drug should be used when?. (27th July 2018) - Ghatalia, Pooja; Zibelman, Matthew; Geynisman, Daniel M.; Plimack, Elizabeth
The treatment of advanced metastatic urothelial carcinoma has recently evolved with the approval of five checkpoint inhibitors. In the second-line setting, in patients who have progressed on cisplatin-based chemotherapy, pembrolizumab, atezolizumab, durvalumab, nivolumab and avelumab are United States Food and Drug Administration (FDA) approved. In cisplatin-ineligible patients, atezolizumab and pembrolizumab are the FDA-approved checkpoint inhibitors. Here we describe the updated clinical efficacy of these checkpoint inhibitors in the treatment of advanced urothelial carcinoma and then suggest how they can be sequenced in the context of available chemotherapeutic options. For cisplatin-eligible patients, platinum-based chemotherapy remains the standard first-line treatment. For patients progressing on platinum-based therapy, phase III trials have been performed comparing pembrolizumab and atezolizumab separately with standard chemotherapy, and results favor the use of pembrolizumab.